Professor K. Zhubanov and terminography dictionary compiled based on its 10 principles (Eurasian Journal of Philology Science and Education, 2016)
This article is about works of Professor, nomenclature K. Zhubanov and a scientific analysis of «Physiology of vegetable» glossary which written in 1930-1990. At first K. Zhubanov’s 10 principles are translated accordingly to the desire researcher. Structure and system of this glossary are based on these principles. With this structures and systems of glossaries in 1930-1990 described a view which K. Zhubanov. A political image of kazakh terminography is proved by specific dictionary. Terms from glossary «Physiology of vegetable» are reached completely.
Keywords: erminografiya; principle; terminological dictionary; memterminok.